Low-magnetic-loss magnetic core manufacturing process
By adjusting the particle size of Fe-Si-Al powder and the amount of insulating coating, combined with the alumina cladding layer and optimized forming pressure and heat treatment conditions, the problem of high magnetic loss of existing soft magnetic materials is solved, and lower magnetic loss and better soft magnetic properties are achieved.
Patent Information
- Application Number
- CN202411733833.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-29
AI Technical Summary
There is still room for improvement in the magnetic loss of existing soft magnetic materials, especially in high-frequency working environments.
The magnetic powder core is prepared by using Fe-Si-Al powder. By adjusting the particle size of the powder and the amount of insulating coating agent, combined with alumina as an inorganic coating agent, the forming pressure and heat treatment conditions of the magnetic powder core are optimized to reduce magnetic loss.
Through this process, the magnetic loss of the magnetic powder core is significantly reduced, and better soft magnetic properties are obtained especially under medium and high frequency and high Bm conditions.
Smart Images

Figure CN119650286A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnetic material production technology, in particular to a low magnetic loss magnetic core manufacturing process. Background Art
[0002] With the development of electronic devices, communication information and new energy, the demand for functional materials in electronic equipment is increasing, and the performance requirements are also increasing. As one of the most popular functional materials in recent years, soft magnetic materials have received widespread attention. Soft magnetic materials refer to materials that are easy to magnetize and demagnetize. They are widely used in the power and electronic industries, mainly playing the role of information conversion, transmission and storage. The performance parameters that characterize soft magnetic materials mainly include: saturation magnetization (Ms), Curie temperature (Tc), magnetostriction coefficient (λ), magnetocrystalline anisotropy constant (K), magnetic permeability (μ) and coercivity (Hc). Ms, Tc, λ and K are microstructure insensitive parameters that reflect the essential characteristics of the material, which are mainly determined by the material composition and crystal structure. μ and Hc are microstructure sensitive parameters. When the composition and crystal structure are determined, they largely depend on structural factors such as impurities, pores, grain orientation and grain size in the material, as well as external factors such as temperature, radiation and stress. The preparation and processing of soft magnetic materials have a great influence on these microstructure sensitive parameters. The basic performance requirements of soft magnetic materials are: high saturation magnetic induction intensity, high magnetic permeability, high resistivity, good stability, low coercive force, low magnetic loss, low magnetostriction coefficient and low magnetocrystalline anisotropy constant.
[0003] Based on this, Chinese patent CN104321839B discloses a soft magnetic composite (SMC) material, which is formed by atomized ferromagnetic particles. Particles with a predetermined size range are formed, and the particles are coated with at least one layer of electrically insulating nanoscale inorganic filler to form an insulating ferromagnetic powder as an SMC material. The particles are further coated with a lubricant to facilitate demolding.
[0004] However, the magnetic loss of the soft magnetic materials disclosed above still has room for improvement. Specifically, the metal soft magnetic powder core refers to a material made by mixing and pressing metal or alloy soft magnetic powder and insulating medium. The application and development of metal soft magnetic powder cores meet the requirements of electronic devices to develop in the direction of high efficiency, high power and miniaturization. Metal soft powder cores mainly include Fe powder cores, Fe-Si powder cores, Fe-Si-AI powder cores, high flux magnetic powder cores and platinum permalloy magnetic powder cores. The soft magnetic materials disclosed in the prior art can be used for the production of Fe powder cores; the Fe powder cores are made of high-purity Fe powder or hydroxy iron powder as raw materials, and are prepared through coating, pressing and annealing. This powder core has a simple preparation process, cheap raw materials, good magnetic properties, and is the most widely used and largest-volume metal soft magnetic powder core. Among them, the saturation flux density of the Fe powder core is relatively high, reaching 0.5T~1.3T, and the range of magnetic permeability is 10~100o. However, the disadvantages of Fe powder cores are also obvious, including low resistivity, poor DC bias characteristics and poor magnetic loss. At present, the resistivity of Fe powder cores can be improved by mixing them with ferrite powder to make composite Fe powder cores. This method can reduce the magnetic loss of Fe powder cores in high-frequency working environments, but the improvement effect is not obvious. Summary of the invention
[0005] Based on this, it is necessary to provide a low magnetic loss magnetic core manufacturing process to address the technical problem of how to reduce the magnetic loss of the magnetic core.
[0006] A low magnetic loss magnetic core manufacturing process, comprising the following steps: S1, preparing Fe-Si-AI powder with a preset particle size; S2, mixing the powder according to a preset ratio; S3, insulating and coating the powder; S4, pressing and molding the insulating and coated powder; S5, heat treating the magnetic powder core green body obtained by pressing; Wherein, the process of step S3 is: S31, prepare a passivation solution, weigh 0.6 g to 2.0 g of phosphoric acid, put it into a reactor, add 20 ml of C3H60 and stir to completely dissolve the phosphoric acid; S32, weigh 100g of powder and put it into the reactor, and continue to stir to make the powder passivated evenly; then put the reactor into an electric blast drying oven, set the drying oven temperature to 80°C, and dry the powder for 2h; S33, sieving the dried powder with an 80-mesh sieve, adding 4‰ of resin and a release agent to the sieve, mixing evenly, and then bagging and sealing the prepared Fe-Si-AI powder mixture for storage; The process of step S4 includes: using a 160-ton hydraulic press to load the prepared powder mixture into a mold, setting the pressure of the press to 1860 MPa, and pressing to obtain a magnetic powder core green body; The process of step S5 includes: loading the Fe-Si-AI magnetic powder core green body into an annealing furnace, setting the maximum furnace temperature to 730° C., annealing time to 4 hours, and naturally cooling the annealed magnetic powder core.
[0007] Specifically, the particle sizes of the Fe-Si-AI powders prepared in step S1 are D50=5 μm, D50=35 μm or D50=90 μm.
[0008] Specifically, in step S2, the components of the Fe-Si-AI powder are, by mass, 85 parts of Fe, 9.6 parts of Si, and 5.4 parts of AI.
[0009] Specifically, for the magnetic powder core prepared by Fe-Si-AI powder with D50=90μm, the amount of phosphoric acid used is 1.2wt%; for the magnetic powder core prepared by Fe-Si-Al powder with D50=35μm, the amount of phosphoric acid used is 1.0wt%; for the magnetic powder core prepared by Fe-Si-AI powder with D50=5μm, the amount of phosphoric acid used is 1.0wt%.
[0010] Further, in another embodiment, the process of step S3 is changed to: S31, prepare a buffer solution, weigh 4 g of Na2CO3 and 100 ml of deionized water, respectively, and mix and stir until the solution is clear; S32, continue to prepare the aluminum source solution, first weigh 2g to 11g of A1(N03)3·9H2O and put it into the reactor, then add 100ml of C2H5OH into the reactor and stir until A1(N03)3·9H2O is completely dissolved and then pour it into the three-necked reactor; S33, then, weigh 50 g of Fe-Si-AI powder with D50=5 μm, pour it into the three-necked reactor, and stir for 10 min; S34, then, adding a pH buffer solution to the three-necked reactor to adjust the pH of the mixed solution to 4, and then heating the mixed solution in a water bath at 50° C., stirring for 4 h, filtering, washing, and drying; S35, then, the above preliminarily coated metal powder is sieved with a 200-mesh sieve and poured into a crucible, and placed in a tubular furnace for annealing; the atmosphere is argon, the annealing temperature is set to a maximum of 500° C., the heating rate is 5° C. / min, and the furnace is cooled.
[0011] Furthermore, in another embodiment, the process of step S4 is changed to: sieve the heat-treated metal powder with an 80-mesh sieve, add 8‰ of resin and 4‰ of release agent to the material under the sieve; then, mix them evenly; place the mixture into a mold by compression molding, and press mold it at pressures of 1705MPa, 1860MPa, 2015MPa and 2170MPa, respectively, to obtain alumina-coated Fe-Si-AI powder core green body.
[0012] Furthermore, in another embodiment, the process of step S5 is changed to: loading the pressed Fe-Si-AI magnetic powder core green body into an annealing furnace, the annealing temperature is 730° C., the annealing time is 4 hours, and the annealed magnetic powder core is cooled along with the furnace.
[0013] Furthermore, in another embodiment, when the soft magnetic powder core is prepared from Fe-Si-AI powder with a particle size of D50=5 μm, the amount of alumina used is 2.0 wt % and the molding pressure is 1860 MPa.
[0014] In summary, the present invention discloses a low magnetic loss magnetic core manufacturing process, which reveals the influence of three Fe-Si-AI powder particle sizes of D50=90μm, D50=35μm and D50=5μm and the amount of insulating agent, namely phosphoric acid, on the medium and high frequency soft magnetic properties of the magnetic powder core, and obtains the optimal powder particle size selection under medium and high frequency and high power. Afterwards, using alumina as an inorganic coating agent, the influence of the amount of alumina raw material and the molding pressure on the medium and high frequency soft magnetic properties of the magnetic powder core is revealed. By comparing the magnetic properties of the magnetic powder cores coated with two inorganic coating agents, namely alumina and phosphoric acid, an improvement scheme for the alumina coating layer is proposed. In the magnetic powder core prepared by Fe-Si-AI powder with D50=5μm coated with alumina, the density and effective magnetic permeability of the magnetic powder core decrease with the increase of alumina dosage and increase with the increase of molding pressure. The DC bias performance increases with the increase of alumina dosage and decreases with the increase of molding pressure. The magnetic loss first decreases and then increases with the increase of the amount of alumina and the molding pressure. Moreover, the best soft magnetic performance powder core can be obtained when the amount of alumina is 2.0wt% and the molding pressure is 1860MPa. The Fe-Si-AI magnetic powder core obtained by this process has the lowest magnetic loss. Therefore, the low magnetic loss magnetic core manufacturing process of the present invention solves the technical problem of how to reduce the magnetic loss of the magnetic core. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 The present invention is a flowchart of a low magnetic loss magnetic core manufacturing process. DETAILED DESCRIPTION
[0015] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0016] Specifically, the metal soft magnetic powder core is mainly prepared by powder metallurgy process. This process can be described as pressing the alloy magnetic powder with surface insulation coating into a green body under a certain pressure, and then releasing the residual stress in the green body through heat treatment. The preparation process of metal soft magnetic powder core is mainly divided into the following Figure 1 The process shown.
[0017] Specifically, in the preparation process of metal powder, the morphology of metal powder has a great influence on the performance of the prepared soft magnetic powder core, mainly affecting the magnetic properties by affecting the insulation coating effect and the pressing molding effect. At present, there are two main methods for preparing metal soft magnetic powder: mechanical ball milling and atomization. Mechanical ball milling is to prepare alloy ingots into metal powder by physically destroying the binding force between metal atoms. Atomization can be divided into gas atomization and water atomization. It blows liquid metal into powder by high-pressure airflow and water flow. The surface composition of the powder prepared by this method is different from that of the original alloy. The powder prepared by gas atomization is generally regular spherical, with a relatively smooth surface and scaly. The powder prepared by water atomization presents an irregular spherical shape, and the oxygen content on the powder surface is high. Compared with the two methods, the cost of preparing soft magnetic powder by mechanical ball milling is lower, and the powder pressing moldability is better. However, the prepared powder has edges and corners, and the coating layer is easily damaged in the subsequent insulation coating. The soft magnetic powder prepared by the gas atomization method is regular spherical, easy to coat and has excellent integrity of the coating layer, but the pressing effect is poor, especially when the powder particle size is small, it is extremely difficult to form. Compared with gas atomization, the soft magnetic powder prepared by water atomization has better formability, and the magnetic permeability of the prepared soft magnetic powder core is also higher, but the magnetic loss is also higher. It is worth mentioning that the flaky magnetic powder prepared by the ball milling method has a larger aspect ratio than the irregular crushed magnetic powder and the atomized magnetic powder, and can maintain a higher magnetic permeability in the high-frequency range while having low eddy current loss, which is beneficial to the material's absorption of high-frequency electromagnetic waves.
[0018] Among them, in the powder particle size ratio process, in the process of preparing metal soft magnetic powder cores, the powder particle size distribution has a great influence on the magnetic properties of the soft magnetic powder core. Generally, large-particle powder has good fluidity, can reduce the air void ratio inside the powder core, and increase the density and magnetic permeability of the powder core, but the DC bias performance of the powder core deteriorates. Small-particle powder has increased friction between particles and poor fluidity, which increases the air void ratio inside the prepared powder core, reduces the density and magnetic permeability of the powder core, but improves the DC bias characteristics. Appropriate particle size distribution can promote the reasonable matching of powders of various particle sizes, reduce the air void ratio inside the powder core, and reduce the effective demagnetization field inside the powder core, thereby increasing the density and magnetic permeability of the powder core and reducing hysteresis loss.
[0019] Among them, in the insulation coating process of the powder, the insulation coating of the powder in the preparation process of the soft magnetic powder core is the core of the whole process. Compared with other soft magnetic materials, the advantage of the metal soft magnetic powder core is that the insulation layer on the powder surface and the air gap between the powders can greatly improve the DC bias performance. The effect of the insulation coating on the soft magnetic powder core can be divided into two aspects. First, the non-magnetic insulation layer can increase the effective demagnetization field inside the powder core, enhance the DC bias performance of the powder core, and increase the anti-saturation performance of the powder core. Secondly, the insulation coating layer on the surface of the powder can block the eddy current path generated under the alternating magnetic field and reduce the eddy current loss generated by the powder core at high frequency. The insulation coating method is mainly divided into organic coating and inorganic coating. The organic insulation coating layer is mainly various resins. This coating method has a relatively simple process, but it is not resistant to high temperature. The resin is easy to decompose during the annealing process of the powder core. Therefore, the annealing temperature of the resin-coated powder core cannot exceed 500°C, which will cause the stress inside the powder core to not be completely released, increasing the coercive force and hysteresis loss. There are two types of inorganic coating. One is to use the passivation liquid to react with the surface of the powder to form a passivation layer, such as phosphoric acid passivation. This method is relatively simple and has a good coating effect, but it is not suitable for soft magnetic powders with good corrosion resistance, such as Fe-Ni powder. The other is to use various oxides to evenly wrap the powder to form a dense coating layer, such as A12O3, SiO2, MgO, etc. However, this method is more complicated; and the coating layer is easy to fall off, so it is not suitable for crushing powder.
[0020] Among them, in the process of pressing and molding, the soft magnetic powder core is generally prepared by powder metallurgy, and pressing and molding is a crucial step. Resin and release agent are generally added to the powder before pressing and molding. The resin is used to increase the adhesion between the powders, making the green body easier to mold and the surface layer not easy to fall off. The release agent is used to make the pressed green body easy to demold and not pull the mold, thereby increasing the service life of the mold. The mixed powder is generally pressed and molded by molding. The factor that affects the magnetic properties of the powder core during the pressing and molding process is the pressing pressure. The greater the pressure, the higher the density of the powder core, the smaller the internal air gap ratio, the smaller the effective demagnetization field inside the powder core, the higher the magnetic permeability of the powder core, and the smaller the hysteresis loss. However, excessive pressing strength will destroy the insulating layer on the surface of the powder, increase residual stress, and deteriorate the magnetic properties of the powder core.
[0021] Among them, in the heat treatment process, the purpose of heat treating the pressed green body is to eliminate the residual stress inside the powder core, decompose organic matter, increase the overall strength of the powder core, etc. The heat treatment process parameters include heat treatment temperature, heating rate, heat treatment atmosphere, holding time, and cooling time. The magnetic properties of the soft magnetic powder core are very sensitive to the heat treatment temperature. Too low temperature will cause incomplete release of residual stress and increase the coercive force of the powder core. Too high temperature will decompose the coating layer, fail to effectively block the eddy current between particles, and deteriorate the magnetic properties of the powder core. Only the right temperature can achieve the purpose of eliminating internal stress and defects. The heat treatment process generally uses gases such as N2 or Ar as protective gases to protect the green body from oxidation during the annealing process.
[0022] Specifically, the present invention provides a low magnetic loss magnetic core manufacturing process, wherein the main process steps of one embodiment include: S1, preparing Fe-Si-AI powder with a preset particle size; S2, mixing the powder according to a preset ratio; S3, insulating and coating the powder; S4, pressing and molding the powder after the insulation coating; S5, heat treating the magnetic powder core green body obtained by pressing; Wherein, in step S3, the following steps are specifically included: S31, prepare a passivation solution, weigh 0.6 g to 2.0 g of phosphoric acid, put it into a reactor, add 20 ml of C3H60 and stir to completely dissolve the phosphoric acid; S32, weigh 100g of powder and put it into the reactor, and continue to stir to make the powder passivated evenly; then put the reactor into an electric blast drying oven, set the drying oven temperature to 80°C, and dry the powder for 2h; S33, the dried powder is sieved with an 80-mesh sieve, and the sieve is added with 4‰ of resin and release agent, i.e. C 36 H 70 O4Zn, and then the prepared Fe-Si-AI powder mixture is packed and sealed for storage; Among them, in step S4, the specific process includes: using a 160-ton hydraulic press to load the prepared powder mixture into a mold, setting the pressure of the press to 1860 MPa, and pressing to obtain a magnetic powder core green body; Among them, in step S5, the specific process includes: loading the Fe-Si-AI magnetic powder core green body into an annealing furnace, setting the maximum furnace temperature to 730° C., annealing time to 4 hours, and naturally cooling the annealed magnetic powder core.
[0023] Specifically, soft magnetic composite materials composed of various metal magnetic powders and insulating materials, referred to as SMC, have been widely used in power electronic devices such as reactors and inverters. Compared with traditional soft magnetic materials such as silicon steel and ferrite, SMC has the advantages of low eddy current loss, high DC bias performance and high magnetic flux density. In order to further reduce the eddy current loss of SMC and improve the anti-saturation ability, the prior art discloses different insulation methods to block the magnetic circuit between the eddy current path and the magnetic powder. However, with the increase of the frequency and power of electronic equipment, it becomes more difficult to reduce the medium and high frequency loss and improve the anti-saturation ability only by optimizing the insulation quality of the powder. In order to solve this problem, a low magnetic loss magnetic core manufacturing process of the present invention combines the two approaches of insulation coating process and powder particle size regulation, and compares the magnetic properties of powder cores prepared from Fe-Si-AI powders with different particle sizes, and obtains the best choice under different frequencies and external magnetic fields. In the process scheme of the present invention, phosphoric acid can be used as a passivating agent, and the amount used is in the range of 0.6wt% to 2.0wt%. The selected Fe-Si-AI powder can be pre-prepared into different states with particle sizes of D50=5μm, D50=35μm and D50=90μm; in addition, in the subsequent steps, the ratio of the Fe-Si-AI metal powder is as follows: 85 parts of Fe, 9.6 parts of Si and 5.4 parts of AI, calculated by mass. First, the present invention will reveal the effect of the amount of phosphoric acid on the magnetic properties of the powder core, and then select the embodiments of the same phosphoric acid amount passivation and the same magnetic permeability, compare their soft magnetic properties in different frequency and power ranges, and derive the effect of the passivation amount and powder particle size on the soft magnetic properties of the powder core.
[0024] Specifically, from the test results of different embodiments, it can be seen that as the amount of phosphoric acid increases, the magnetic permeability of the magnetic powder core gradually decreases, and the DC bias performance becomes better. Among them, the magnetic powder core prepared by using Fe-Si-AI powder with D50=90μm has the lowest magnetic loss when the amount of phosphoric acid used is 1.2wt%; the magnetic powder core prepared by using Fe-Si-Al powder with D50=35μm has the lowest magnetic loss when the amount of phosphoric acid used is 1.0wt%; and the magnetic powder core prepared by using Fe-Si-AI powder with D50=5μm has the lowest magnetic loss when the amount of phosphoric acid used is 1.0wt%.
[0025] Furthermore, under the conditions of medium and high frequencies and high Bm, metal powders with small particle sizes help to increase the resistivity of the magnetic powder core, thereby limiting eddy currents and effectively reducing magnetic losses. In addition, although the effective magnetic permeability of the magnetic powder core prepared by small particle size powder is low, good DC bias performance can be obtained. The reason is that small particle size and low density bring about a large effective demagnetization field. When the magnetic permeability is adjusted to the same, since the effective demagnetization field inside the magnetic powder core is similar, the particle size has little effect on the anti-saturation ability and magnetic loss under low frequencies and low Bm, but by reducing the particle size, the loss of the powder core under medium and high frequencies and high Bm can still be greatly reduced.
[0026] Furthermore, in another embodiment of a low magnetic loss magnetic core manufacturing process of the present invention, step S1 and step S2 are the same as those in the above embodiment, but the specific implementation methods of step S3 to step S5 are different; specifically, as follows: In step S3 of this embodiment, the following steps are specifically included: S31, prepare a buffer solution, weigh 4 g of Na2CO3 and 100 ml of deionized water, respectively, and mix and stir until the solution is clear; S32, continue to prepare the aluminum source solution, first weigh 2g to 11g of A1(N03)3·9H2O and put it into the reactor, then add 100ml of C2H5OH into the reactor and stir until A1(N03)3·9H2O is completely dissolved and then pour it into the three-necked reactor; S33, then, weigh 50 g of Fe-Si-AI powder with D50=5 μm, pour it into the three-necked reactor, and stir for 10 min; S34, then, adding a pH buffer solution to the three-necked reactor to adjust the pH of the mixed solution to 4, and then heating the mixed solution in a water bath at 50° C., stirring for 4 h, filtering, washing, and drying; S35, then, the above preliminarily coated metal powder is sieved with a 200-mesh sieve and poured into a crucible, and then placed in a tube furnace for annealing; the atmosphere is Ar gas inert gas, the annealing temperature is set to a maximum of 500° C., the heating rate is 5° C. / min, and the crucible is cooled with the furnace; Next, in step S4, the heat-treated metal powder is sieved with an 80-mesh sieve, and 8‰ of resin and 4‰ of a release agent are added to the sieved material; then, the mixture is mixed evenly; the mixture is placed in a mold by compression molding, and is pressed at pressures of 1705 MPa, 1860 MPa, 2015 MPa, and 2170 MPa, respectively, to obtain Fe-Si-AI powder core green bodies coated with alumina; Next, in step S5, the pressed Fe-Si-Al magnetic powder core green body is loaded into an annealing furnace, the annealing temperature is 730°C, the annealing time is 4 hours, and the annealed magnetic powder core is cooled in the furnace.
[0027] Specifically, from the experimental results of the previous embodiment, it can be seen that the magnetic powder core prepared by metal powder with small particle size can reduce the medium and high frequency magnetic loss and improve the anti-saturation performance. Therefore, in order to further reduce the medium and high frequency magnetic loss of Fe-Si-AI magnetic powder cores to improve the comprehensive soft magnetic properties; in this embodiment, a high resistivity oxide is used to coat small particle size powder to prepare soft magnetic powder cores. At present, commonly used oxide coatings include aluminum oxide, silicon oxide, etc., and the coating methods generally used are hydrolysis, co-precipitation, or a mixture of nano-oxide powder and magnetic powder. The oxide process does not react with magnetic powder, so it is expected to achieve better insulation coating for alloy powders with good corrosion resistance. Because there are a lot of existing technologies for verifying the preparation of soft magnetic powder cores by coating magnetic powder with silicon oxide, and this embodiment uses aluminum oxide with higher theoretical resistivity as the coating layer, and the method used is A1 3+ Hydrolysis method: The medium and high frequency magnetic loss of the powder core is reduced by coating the small-sized Fe-Si-AI powder with high resistivity alumina.
[0028] Specifically, the latter embodiment is implemented by A1 3+ The Al(OH)3 is prepared by hydrolysis to initially coat the magnetic powder, and then most of the Al(OH)3 on the surface of the metal powder is decomposed into alumina by heat treatment. Among them, it can be seen from the experimental results that with the increase of the amount of alumina, the density and effective magnetic permeability of the Fe-Si-AI magnetic powder core gradually decrease, the DC bias performance improves, and the magnetic loss shows a trend of first decreasing and then increasing. This is because with the increase of the amount of alumina, the non-magnetic material and air gap ratio in the magnetic powder core increase, which enhances the effective demagnetization field inside the powder core and reduces the density and effective magnetic permeability of the powder core. However, the increase in the effective demagnetization field also enhances the DC bias performance of the magnetic powder core and improves the anti-saturation performance of the magnetic powder core. The change in magnetic loss is related to the coating layer on the surface of the powder. If the coating amount is too small and the coating layer is uneven, large eddy current loss and residual loss will be generated. If the coating amount is too large and the coating layer is too thick, large hysteresis loss will be generated; therefore, choosing a suitable coating amount can effectively reduce magnetic loss. In summary, the magnetic powder core with the lowest magnetic loss can be obtained when the alumina coating amount is 2.0wt%.
[0029] Furthermore, the molding pressure will also affect the magnetic properties of the Fe-Si-AI magnetic powder core coated with alumina. As the molding pressure increases, the density of the magnetic powder core gradually increases because the air gap inside the magnetic powder core decreases. This also proves that the structural demagnetization field generated by the air gap gradually decreases, so the magnetic permeability of the magnetic powder core gradually increases, and the DC bias performance decreases. The effect of molding pressure on the magnetic loss of the magnetic powder core is mainly determined by the air gap inside the magnetic powder core and the quality of the powder surface coating layer. Small molding pressure makes the powder core have a larger air gap, resulting in a larger hysteresis loss of the powder core. Large molding pressure destroys the insulating layer on the surface of the powder, increasing the eddy current loss and residual loss of the powder core. Therefore, for the coated magnetic powder core, a suitable molding pressure is extremely important. In this embodiment, a molding pressure of 1860MPa is selected to obtain a soft magnetic powder core with the lowest magnetic loss.
[0030] In general, this example can prove that the use of alumina-coated Fe-Si-AI powder with D50=5μm to prepare soft magnetic powder cores can reduce magnetic losses at medium and high frequencies and optimize anti-saturation performance. The optimal preparation conditions are: 2.0wt% alumina and a molding pressure of 1860MPa. The magnetic permeability of the magnetic powder core obtained by this method is about 62. When the external DC magnetic field strength is 8000A / m, the %μe of the magnetic powder core is as high as 63.85, and the magnetic loss at 200kHz / 50mT is 235.8mW / cm 3 , can achieve excellent performance levels.
[0031] In summary, the present invention discloses a low magnetic loss magnetic core manufacturing process, which reveals the influence of three Fe-Si-AI powder particle sizes of D50=90μm, D50=35μm and D50=5μm and the amount of insulating agent, namely phosphoric acid, on the medium and high frequency soft magnetic properties of the magnetic powder core, and obtains the optimal powder particle size selection under medium and high frequency and high power. Afterwards, using alumina as an inorganic coating agent, the influence of the amount of alumina raw material and the molding pressure on the medium and high frequency soft magnetic properties of the magnetic powder core is revealed. By comparing the magnetic properties of the magnetic powder cores coated with two inorganic coating agents, namely alumina and phosphoric acid, an improvement scheme for the alumina coating layer is proposed. In the magnetic powder core prepared by Fe-Si-AI powder with D50=5μm coated with alumina, the density and effective magnetic permeability of the magnetic powder core decrease with the increase of alumina dosage and increase with the increase of molding pressure. The DC bias performance increases with the increase of alumina dosage and decreases with the increase of molding pressure. The magnetic loss first decreases and then increases with the increase of the amount of alumina and the molding pressure. Moreover, the best soft magnetic performance powder core can be obtained when the amount of alumina is 2.0wt% and the molding pressure is 1860MPa. The Fe-Si-AI magnetic powder core obtained by this process has the lowest magnetic loss. Therefore, the low magnetic loss magnetic core manufacturing process of the present invention solves the technical problem of how to reduce the magnetic loss of the magnetic core.
[0032] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0033] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A process for manufacturing a low magnetic loss magnetic core, characterized in that: The method comprises the following steps: S1, preparing Fe-Si-AI powder of a preset particle size; S2, mixing the powder according to a preset ratio; S3, insulating and coating the powder; S4, pressing and molding the powder after the insulation coating; S5, heat treating the magnetic powder core green body obtained by pressing; Wherein, the process of step S3 is: S31, prepare a passivation solution, weigh 0.6 g to 2.0 g of phosphoric acid, put it into a reactor, add 20 ml of C3H60 and stir to completely dissolve the phosphoric acid; S32, weigh 100g of powder and put it into the reactor, and continue to stir to make the powder passivated evenly; then put the reactor into an electric blast drying oven, set the drying oven temperature to 80°C, and dry the powder for 2h; S33, sieving the dried powder with an 80-mesh sieve, adding 4‰ of resin and a release agent to the sieve, mixing evenly, and then bagging and sealing the prepared Fe-Si-AI powder mixture for storage; The process of step S4 includes: using a 160-ton hydraulic press to load the prepared powder mixture into a mold, setting the pressure of the press to 1860 MPa, and pressing to obtain a magnetic powder core green body; The process of step S5 includes: loading the Fe-Si-AI magnetic powder core green body into an annealing furnace, setting the furnace temperature to a maximum temperature of 730° C., annealing time of 4 hours, and naturally cooling the annealed magnetic powder core.
2. A low magnetic loss magnetic core manufacturing process according to claim 1, characterized in that: The particle sizes of the Fe-Si-AI powders prepared in step S1 are D50=5 μm, D50=35 μm or D50=90 μm.
3. A low magnetic loss magnetic core manufacturing process according to claim 2, characterized in that: In step S2, the components of the Fe-Si-AI powder are, by mass, 85 parts of Fe, 9.6 parts of Si, and 5.4 parts of AI.
4. The low magnetic loss core manufacturing process according to claim 3 is characterized in that: For the magnetic powder core prepared by Fe-Si-AI powder with D50=90μm, the amount of phosphoric acid used is 1.2wt%; for the magnetic powder core prepared by Fe-Si-Al powder with D50=35μm, the amount of phosphoric acid used is 1.0wt%; for the magnetic powder core prepared by Fe-Si-AI powder with D50=5μm, the amount of phosphoric acid used is 1.0wt%.
5. The low magnetic loss magnetic core manufacturing process according to claim 3, characterized in that: The process of step S3 is changed to: S31, prepare a buffer solution, weigh 4 g of Na2CO3 and 100 ml of deionized water, respectively, and mix and stir until the solution is clear; S32, continue to prepare the aluminum source solution, first weigh 2g to 11g of A1(N03)3·9H2O and put it into the reactor, then add 100ml of C2H5OH into the reactor and stir until A1(N03)3·9H2O is completely dissolved and then pour it into the three-necked reactor; S33, then, weigh 50 g of Fe-Si-AI powder with D50=5 μm, pour it into the three-necked reactor, and stir for 10 min; S34, then, adding a pH buffer solution to the three-necked reactor to adjust the pH of the mixed solution to 4, and then heating the mixed solution in a water bath at 50° C., stirring for 4 h, filtering, washing, and drying; S35, then, the above preliminarily coated metal powder is sieved with a 200-mesh sieve and poured into a crucible, and placed in a tubular furnace for annealing; the atmosphere is argon, the annealing temperature is set to a maximum of 500° C., the heating rate is 5° C. / min, and the furnace is cooled.
6. The low magnetic loss magnetic core manufacturing process according to claim 5, characterized in that: The process of step S4 is changed to: sieve the heat-treated metal powder with an 80-mesh sieve, add 8‰ of resin and 4‰ of release agent to the sieve; then, mix them evenly; place the mixture into a mold by compression molding, and press mold it at pressures of 1705MPa, 1860MPa, 2015MPa and 2170MPa, respectively, to obtain alumina-coated Fe-Si-AI powder core green body.
7. The low magnetic loss magnetic core manufacturing process according to claim 6, characterized in that: The process of step S5 is changed to: the pressed Fe-Si-AI magnetic powder core green body is loaded into an annealing furnace, the annealing temperature is 730° C., the annealing time is 4 hours, and the annealed magnetic powder core is cooled along with the furnace.
8. The low magnetic loss core manufacturing process according to claim 1, characterized in that: When preparing soft magnetic powder cores with Fe-Si-AI powder with a particle size of D50=5μm, the amount of alumina is 2.0wt% and the molding pressure is 1860MPa.
Citation Information
Patent Citations
Soft Magnetic Composite
CN104321839B
Low-loss iron-silicon-aluminum magnetic powder core composite coating method
CN109461558A
Preparation method of compact aluminum oxide coated soft magnetic powder
CN113674983A
Preparation method of gas atomization Fe-Si-Al metal soft magnetic powder core
CN116313479A
Fe-based amorphous magnetic powder, magnetic powder core with excellent high frequency properties and method of making them
US20070258842A1
Cited By
Process for producing metal magnetic powder core APC gas atomization Fe-Si-Al
CN119681262A